If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 61 = -59 Reorder the terms: 61 + 10x = -59 Solving 61 + 10x = -59 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-61' to each side of the equation. 61 + -61 + 10x = -59 + -61 Combine like terms: 61 + -61 = 0 0 + 10x = -59 + -61 10x = -59 + -61 Combine like terms: -59 + -61 = -120 10x = -120 Divide each side by '10'. x = -12 Simplifying x = -12
| 5.25+b=22.75 | | 8x+16=100 | | 40-6x=-116 | | g(x)=1482 | | 0.5x*10=0.15 | | 14n^2/2n^2 | | -5(x-6)=-34+3x | | 3m-m^2=2 | | -18x+102=354 | | 0.6-4=2.6 | | 10=0.10x | | 9x+27=100 | | 10/0.10 | | 8+8m=4+8m+8 | | 8+8m=4+8m+4 | | 3x-2+4=70 | | 5n-n=15+7 | | 7x-x=-16-2x | | -7r-8-5r=-13-7r | | 9x+45=100 | | f(x)=(x^7-4x^6)*(x+3)*(x-2) | | 9x+36=100 | | 12+3m=7m-2m | | 8x+32=100 | | v+4=-12+1-v-1 | | 10=4-5n+4n | | 7x+28=100 | | 7x+21=100 | | 2x-3-6x=-7x-6 | | 7x+14=100 | | x-6=-14-x | | 3x+6x-10=53 |